2010
DOI: 10.1159/000321832
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Tumour Necrosis Factor-Alpha and Interleukin-6 in Severely Ill Patients with Eating Disorders

Abstract: Background: The underlying pathophysiology of eating disorders (ED) is dependent on complex interactions between psychological, biological and social factors. The purpose of the present study was to examine a possible increase in cytokines indicating inflammation, as measured by tumour necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in ED patients, and to explore possible relationships between cytokines and self-reported personality traits. Methods: Female patients with severe ED (n = 26) were recruited con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…Study and sample characteristics are presented in Table 1. Two studies included multiple ED subgroups (Ahrén-Moonga et al, 2011;Brambilla et al, 1998). Twenty-three studies reported cross-sectional comparisons in cytokine concentration between participants with AN (n=538) and HCs, identifying four new studies not included in the previous meta-analysis (Solmi et al, 2015).…”
Section: Characteristics Of Included Studies and Participantsmentioning
confidence: 99%
“…Study and sample characteristics are presented in Table 1. Two studies included multiple ED subgroups (Ahrén-Moonga et al, 2011;Brambilla et al, 1998). Twenty-three studies reported cross-sectional comparisons in cytokine concentration between participants with AN (n=538) and HCs, identifying four new studies not included in the previous meta-analysis (Solmi et al, 2015).…”
Section: Characteristics Of Included Studies and Participantsmentioning
confidence: 99%
“…It is possible that greater disease burdens trigger irritability that can induce depression through mediation of social isolation (Ahrén-Moonga et al, 2011). Bio-behavioral mechanisms of this pathway should be investigated (Wichers & Maes, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to that observed in two studies that measured cytokine concentrations in vivo (Brambilla et al, 1998;Monteleone et al, 1999). Although concentrations of IL-6 and TNF-α have also been found to be elevated in people with BN, compared to HCs in two studies (Ahren-Moonga et al, 2011;Nakai et al, 2000). Binge eating behaviours (as assessed by a range of questionnaires) have also been shown to be significantly and positively associated with TNF-α concentrations in adolescents (Lofrano-Prado et al, 2011).…”
Section: Findings In Bulimia Nervosamentioning
confidence: 95%